THE EFFECT OF WORK MOTIVATION, WORK COMPETENCE AND WORK LOAD ON INCREASING EMPLOYEE PRODUCTIVITY WITH INCENTIVES AS AN INTERVENING VARIABLE AT PT WULING MAJU MOTOR - Adinda Purnama Sari; Bambang Satriawan; Muammar Khaddafi (CV. Radja Publika, 2024)
This study examines the Influence of Work Motivation, Work Competence and Workload on Increasing Employee Productivity with Incentives as Intervening Variables at PT Wuling Maju Motor. This research approach is quantitative research. The data analysis technique in this study uses Partial Least Square (PLS) which is a Multivariate Analysis in the second generation using structural equation modeling (Structural Equation Model/SEM). The results of the study Work Motivation has a significant influence on the Incentive Provision variable. Work Competence has a significant influence on the Incentive Provision variable. Workload has a significant influence on the Incentive Provision variable. Incentive Provision has a significant influence on the Employee Productivity variable. Work Motivation has a significant influence on the Employee Productivity variable. Work Competence has a significant influence on the Employee Productivity variable. Workload has a significant influence on the Employee Productivity variable. Incentive Provision has a positive and significant influence in mediating Work Motivation on Employee Productivity. Incentive Provision has a positive and significant influence in mediating Work Competence on Employee Productivity. The provision of incentives has a positive and significant effect in mediating workload on employee productivity.